PENGARUH GAMIFIKASI BERBASIS WORDWALL TERHADAP MOTIVASI DAN HASIL BELAJAR PJOK SISWA SEKOLAH DASAR - Eni Yusnita Br Pardede; Polintan Rehulina Sembiring (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effect of Wordwall-based gamification on learning motivation and learning outcomes in Physical Education, Sports, and Health (PJOK) among fifth-grade elementary school students. The study employed a quantitative approach using a quasi-experimental method with a One-Group Pretest–Posttest Design. The participants consisted of 22 fifth-grade elementary school students. Data were collected using a learning motivation questionnaire and learning achievement tests administered before (pretest) and after (posttest) the implementation of Wordwall-based learning. The data were analyzed using descriptive and inferential statistics to determine differences in learning motivation and learning outcomes before and after the treatment. The findings indicated an improvement in both students' learning motivation and learning outcomes following the implementation of Wordwall-based gamification. The use of Wordwall created a more interactive, engaging, and enjoyable learning environment, encouraging students to participate actively in the learning process. Therefore, Wordwall-based gamification can serve as an effective digital learning medium to enhance motivation and learning outcomes in elementary school PJOK classes.